The sex education debates - Kendall, Nancy, 1974- (Chicago : The University of Chicago Press, 2013)
Drawing on ethnographic research in five states, the author reveals important differences and surprising commonalities shared by purported antagonists in the sex education wars, and she illuminates the unintended consequences these protracted battles have, especially on teachers and students. Showing that the lessons that most students, teachers, and parents take away from these battles are antithetical to the long-term health of American democracy, she argues for shifting the measure of sex education success away from pregnancy and sexually transmitted infection rates. Instead, she argues, the debates should focus on a broader set of social and democratic consequences, such as what students learn about themselves as sexual beings and civic actors, and how sex education programming affects school-community relations.
Sex education research and policies -- Microanalyses of sex education -- Florida's "It's Great to Wait" campaign: the state as manager, marketer, and moral arbiter -- It's a local thing: sex education as compromise and choice in Wyoming -- No idea is bad, no opinion is wrong, but knowledge is power: sex education in Wisconsin / (coauthored with Kathleen Elliott) -- Engaging diversity: sex education for all in California -- Morality tales: adolescent desire, disease, and fertility in sex education programs -- Men are microwaves, women are crock-pots: gender roles in AOUME and CSE -- What are we doing about the homosexual threat?: scientism, sexual identity, and sexuality education -- Rape as consuming desire and gendered responsibility -- Concluding thoughts: sex education as civics education.
Includes bibliographical references (pages 263-277) and index.
Keywords: Sex instruction -- United States; Sex instruction for teenagers -- United States; Sex instruction -- Government policy -- United States; Sex instruction for teenagers -- Government policy -- United States